2016
DOI: 10.1097/mcc.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Current incidence and outcome of the acute respiratory distress syndrome

Abstract: On the basis of current evidence, it seems that the incidence and overall hospital mortality of ARDS has not changed substantially in the last decade. Independent of the definition used for identification of ARDS patients, reported population-based incidence of ARDS is an order of magnitude lower in Europe than in the USA. Current hospital mortality of combined moderate and severe ARDS reported in observational studies is greater than 40%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
163
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 186 publications
(175 citation statements)
references
References 29 publications
3
163
0
9
Order By: Relevance
“…Although the recent Berlin definition [5] is probably much better than previous ones, there is still a high variability in both epidemiology and clinical outcomes in diverse healthcare settings [4]. In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Although the recent Berlin definition [5] is probably much better than previous ones, there is still a high variability in both epidemiology and clinical outcomes in diverse healthcare settings [4]. In fact, the incidence of ARDS ranges from 1.5 cases per 100 000 [2] to nearly 79 cases per 100 000 [3], with European countries reporting a lower incidence than USA [6]. Moreover, studies from Brazil reported incidence rates ranging from 1.8 to 31 per 100 000 [7,8].…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…The acute respiratory distress syndrome (ARDS) is an acute inflammatory process of the lungs caused by direct or indirect insults to the alveolar-capillary membrane (1)(2)(3)(4)(5), and is associated with an overall mortality ranging from 35% to 50% (6). Pathologically, ARDS is characterized by diffuse alveolar damage (DAD) with injury to the epithelium and endothelium as well as interstitial and alveolar protein-rich edema, inflammatory cellular infiltration, atelectasis, capillary thrombosis, neovascularization, and pulmonary fibrosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Dünya genelinde insidansı 1.5-79/100.000 olarak bildirilmekle birlikte, Avrupa ülkelerinde bu oran Amerika Birleşik Devletleri (ABD)'den daha düşüktür (2,3,6) . Brezilya'da 2013 tarihli yapılan çok merkezli bir çalışmada, bu oran 100.000'de 1.8 ile 31 bulunmuştur (7,8) .…”
Section: Introductionunclassified